The Romanticism of the Messenger of Allah in the Perspective of the Hadith of the History of Sayyidah 'Aisyah ra - Arif Friyadi Friyadi (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2022)
This article focuses on the figure of Aisyah as the wife of the Prophet and the author of the Hadith. In the midst of this position raises the fundamental question of what the story of her relationship with the Prophet is, whether as a romantic wife or not. So did the Prophet's attitude towards him. To answer this problem, this study tries to read the historical hadiths of Aisyah, whether the romance between the two is reflected in what she narrated. This study used library research with the help of pc software 'Gawami' al-Kalim' and searched using the keyword 'Aisyah'. The results of this study show that categorically, Aisyah narrated a hadith with the theme of romanticism of husband and wife 9 hadiths, namely the nobleness of women menstruating, kissing wives, bathing, combing, stroking, walking, talking, pleasing the wife's heart and comforting menstruating women. These hadiths are not only the Prophet as the perpetrator, but sometimes Aisyah. Therefore, the romance shows that the basic principle of the Prophet's attitude to Aisyah was to glorify, honor and make the wife happy.